The good fight - Quezon, Manuel Luis (D. Appleton-Century company, 1946)
Packed with photos (color and black-and-white), maps, personal stories, and concise, readable descriptions of the major events of World War II, bestselling author Stephen E. Ambrose's The Good Fight is a stunning resource for students of history. Though this horrific war has been written about innumerable times over the last half-century, this chronicle for young readers (14 and older) is one of the most vivid, insightful, and straightforward perspectives around. Ambrose pulls no punches. In the first paragraph of his introduction, he reminds us that "more people were killed, more houses, apartment buildings, factories, bridges, and other works of man were destroyed than ever before or since." From Hitler's rise to power to Japan's attack on Pearl Harbor to the air war over Europe to the War Crimes Trials, the major events of the war are thoughtfully examined and depicted.